Electrochemical Degradation of Alizarin Black Dye in Aqueous Medium using Fe/Al Electrode - Mohammad Salim, Haydar A; Idrees, Shinwar A.; Mohammed Salih, Sabir A.; Rashid, Reving A. (Science Journal of University of Zakho, 2019)
This work investigates the electro-catalytic degradation of alizarinblack dye in an electrochemical cell using Fe as anode and Al as cathode. The influence of initial dye concentration, effect of salt, pH, change of temperature and effect ofchange of applied voltage have been studied in addition, the influence of semiconductor dose has studied as well. In the current work roughly total removal of 70 mg/L of dye occurred in 16 minonly. The results showedthat effect of both electrolyte concentration and applied voltage was positive if combined together and the rate of degradation in neutralmedium was the best for degradation of Alizarin black dye.
Keywords: electro catalytic oxidation; alizarin black dye; semiconductors